Sustainable Production of Liquid Smoke from Coconut Shell Waste Using Controlled Combustion and Agricultural Waste Biofilter - Yongker Baali; Maria Theresia Tulusan; Apriano Saerang; Merry Julia Jamilah Langi (Green Publisher Indonesia, 2026)
Background: This study developed a novel process for producing liquid smoke from coconut shell waste through controlled pyrolysis, optimized by airflow control and a multistage biofilter using agricultural wastes (coconut fiber, rice husk, and coconut shell charcoal). Objective: To optimize liquid smoke production using coconut shell waste, control airflow during pyrolysis, and improve efficiency with an agricultural waste biofilter. Methods: Response Surface Methodology (RSM) identified the optimal conditions: 315 °C temperature, 65-min residence time, and a primary/secondary airflow ratio of 1:1.2. Temperature was the most significant factor, as validated by ANOVA, with a high R² model fit. GC-MS analysis identified 42 chemical compounds, and the condenser design and PID controller ensured efficient condensation and operational stability. Results: Under optimal conditions, the process yielded 68.5 mL/kg with a phenolic content of 93.2 mg GAE/g, a pH of 2.85, and no benzo[a]pyrene. FTIR analysis confirmed the presence of high-quality functional groups in the liquid smoke, including phenolic, guaiacol, 4-ethylphenol, and creosol compounds. The agricultural waste biofilter achieved 78.3% PAH removal and 94.5% phenolic compound retention with low pressure drop and minimal production cost compared to commercial filters. Conclusion: This innovative liquid smoke production process using coconut shell waste and agricultural waste biofilters is sustainable, low cost, and environmentally friendly. It effectively valorizes biomass waste, minimizes pollution, and produces food-grade liquid smoke, supporting the circular economy.